2018
DOI: 10.1002/pc.25001
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and interfacial adhesion of jute, kenaf and E‐glass fabrics reinforcing epoxy composites

Abstract: In this work, three laminated Epoxy composites reinforced with five woven layers of E-glass fabrics, jute fabrics and kenaf fabrics were characterized by broadband dielectric spectroscopy. The dielectric analysis was performed in temperature range from 20 to 180 C and frequency range from 0.1 Hz to 1 MHz. The Epoxy matrix shows the presence of four relaxation processes, which are attributed to the β relaxation process, α relaxation process, the quasi-continuous conduction and the dc conduction. In the laminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…This study revealed that higher adhesion between the reinforcement and the epoxy matrix was achieved with E-glass fabrics. [438] Mayandi et al reported on the effects of chemical treatments, such as sodium hydroxide (NaOH) and calcium hydroxide [Ca (OH) 2 ] and silane coupling agent (NaOH 1 silane) on fibers in composites made from veldt grape fibers (VGFs) with unsaturated polyester (UP) matrix. [439] Nadlene et al reported on the effect of different treatments applied to roselle fibers, which were then used to prepare roselle fiber reinforced vinyl ester composites.…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…This study revealed that higher adhesion between the reinforcement and the epoxy matrix was achieved with E-glass fabrics. [438] Mayandi et al reported on the effects of chemical treatments, such as sodium hydroxide (NaOH) and calcium hydroxide [Ca (OH) 2 ] and silane coupling agent (NaOH 1 silane) on fibers in composites made from veldt grape fibers (VGFs) with unsaturated polyester (UP) matrix. [439] Nadlene et al reported on the effect of different treatments applied to roselle fibers, which were then used to prepare roselle fiber reinforced vinyl ester composites.…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…Whereby, the real part ε ′ was modified into an imaginary part εderiv. The first derivative technique was used in the case of Jute, Kenaf and E‐Glass Fabrics reinforcing epoxy Composites 32 and hybrid unsaturated polyester composites 33 in order to highlight the presence of the interfacial polarization matrix/reinforcement. Figure 9 depicts the derivative εderiv data variation with frequency for all nanocomposites at 100°C.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is more significant at high temperatures. Furthermore, the increase in temperature results in a greater tendency of dipoles to be polarized, usually accompanied by a subtle shift of the relaxation maxima towards higher frequencies [ 51 ]. Overall, the composites reinforced with EXP fibers showed lower values of dielectric strength in comparison with composites reinforced with REF fibers (reduction of Δε from 33.6 to 25.9 at 135 °C for composites with raw 50/50 PP/PBT blend).…”
Section: Resultsmentioning
confidence: 99%